Impact of structured awareness programme on behavioural outcomes regarding ICDS services and its utilization satisfaction among mother with children in selected rural and urban area of Bellary district, Karnataka - P., Rajeswari (International Journal of Contemporary Pediatrics, 2024)
Background: Health, nutrition, yet education are the three basic elements of human resource development, and they are all combined in a unique program known as the integrated development of children service Scheme. Methods: A quasi experimental design where Pre and post-test with equivalent control group design was used to carry out the study. Mothers with children from selected rural and urban area who were fulfilling the inclusion criteria were selected by using non-probability convenient sampling technique. Total 40 samples were included in the study. Results: The study findings revealed the utilization scores of mothers on ICDS service majority mother 335 (83.8%) were not satisfied followed by 65 (16.3%) were moderately satisfied, the pretest and post knowledge scores of subjects in experimental group mean percent of mother on utilization of ICDS service was 37.63% with mean score 14.3 was in pretest, where as in posttest 57.23% with mean score 21.75, the overall pretest and post attitude scores of subjects in experimental group mean percent of mother on utilization of ICDS service was 28.75% with mean score 28.75 and standard deviation 4.610 was in pretest, where as in posttest 46.35% was mean percent, with mean score 46.35 and standard deviation 4.487. Conclusions: The structured awareness programme on ICDS services and its utilization among mothers proved its beneficial effects in terms of satisfaction, awareness and attitude level.